2021
DOI: 10.1111/1365-2745.13657
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of anoxygenic phototrophic bacteria in tank bromeliads exhibit a host‐specific signature

Abstract: Anoxygenic phototrophic bacteria (APB) are a very significant metabolic functional group in the phytotelmata of tank‐forming Bromeliaceae plants. Considering the close relationships existing between the bromeliad and its tank microbiota, the dominance of APB raises the question of their role in the ecology and evolution of these plants. Here, using pufM gene sequencing for taxonomic profiling, we investigated the structure of APB communities in the tanks of five bromeliad species exhibiting different habitat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…Flow cytometry counts enumerated an average of 1.5 ± 1.2 × 10 8 of total cells per milliliter of water in the catchments of D. fullonum (Appendix S1: Section S7). Such microbial cell densities, similar in magnitude to those in the water tanks of the Bromeliaceae (Vergne et al, 2021), are a 100 to 1000 times higher than those recorded in freshwater and marine aquatic systems (Whitman et al, 1998). Our microscopic observations showed that microbial cells were highly abundant around the secretory heads of the club-shaped glandular hairs, but were sparsely distributed between the trichomes (Figure 2A; Appendix S1: Figure S6A).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Flow cytometry counts enumerated an average of 1.5 ± 1.2 × 10 8 of total cells per milliliter of water in the catchments of D. fullonum (Appendix S1: Section S7). Such microbial cell densities, similar in magnitude to those in the water tanks of the Bromeliaceae (Vergne et al, 2021), are a 100 to 1000 times higher than those recorded in freshwater and marine aquatic systems (Whitman et al, 1998). Our microscopic observations showed that microbial cells were highly abundant around the secretory heads of the club-shaped glandular hairs, but were sparsely distributed between the trichomes (Figure 2A; Appendix S1: Figure S6A).…”
supporting
confidence: 64%
“…To our knowledge, these investigations were not pursued by any botanist in the 20th or 21st centuries or, in any case, were not reported in the scientific literature, but drifted into oblivion. During our ongoing research on the microbiome of phytotelmata (Lehours et al, 2016; Vergne et al, 2021), we fortuitously “re”‐discovered the enigmatic filaments of Dipsacus that have no known analog in the plant world. Our primary findings prompted us to further explore past discoveries using modern microscopy and staining methods.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, we cannot disentangle the effect of vegetation type from bromeliad species on microbial composition, because not all bromeliads were found in all forests. Even though some prokaryotic groups may be species-specific ( Vergne et al, 2021 ), our heatmaps of taxonomic groups found along the elevation gradient revealed a distinct clustering of ASVs according to forest type but not bromeliad species. This result suggests that the effect of bromeliad species on prokaryotic composition is minor compared to vegetation type and may be related to changes in the tank environment and not the species per se ( Louca et al, 2017a ).…”
Section: Discussionmentioning
confidence: 76%
“…The microbial communities that form in small pools of water (phytotelmata) interact with their plant hosts in a variety of ways, including providing metabolic services. For example, phototrophic bacteria in bromeliad tanks may provide nitrogen to the plant ( Vergne et al, 2021 ). Conversely, pitcher plants may actively structure their microbial communities in part by providing digestive enzymes to break down prey.…”
Section: Introductionmentioning
confidence: 99%
“…The readily available nutrients that result select for microbial communities that can best utilize them ( Grothjan & Young, 2022 ). Across a range of habitats, bacteria from the genera Proteobacteria and Firmicutes are often found in phytotelmata ( Vergne et al, 2021 ; Yourstone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%